2018
DOI: 10.1177/0954411918760959
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical comparison of transdiscal fixation and posterior fixation with and without transforaminal lumbar interbody fusion in the treatment of L5–S1 lumbosacral joint

Abstract: Transdiscal screw fixation is generally performed in the treatment of high-grade L5-S1 spondylolisthesis. The main thought of the study is that the biomechanical performances of the transdiscal pedicle screw fixation can be identical to standard posterior pedicle screw fixations with or without transforaminal lumbar interbody fusion cage insertion. Lumbosacral portions and pelvises of 45 healthy lambs' vertebrae were dissected. Animal cadavers were randomly and equally divided into three groups for instrumenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…It has many assets, such as a high fusion rate, maintenance of the original disc height, and maintenance of lumbar spine stability [5,6]. Nevertheless, the PS fixation method with interbody fusion has some complications including PS failure, rod breakage, and adjacent segment disease (ASD) as a result of restricting the range of motion (ROM) of the lumbar spine [7][8][9][10]. Many experimental and numerical studies have been conducted based on fusion surgery to benefit from these advantages more efficiently and avoid the disadvantages [11][12][13][14].…”
mentioning
confidence: 99%
“…It has many assets, such as a high fusion rate, maintenance of the original disc height, and maintenance of lumbar spine stability [5,6]. Nevertheless, the PS fixation method with interbody fusion has some complications including PS failure, rod breakage, and adjacent segment disease (ASD) as a result of restricting the range of motion (ROM) of the lumbar spine [7][8][9][10]. Many experimental and numerical studies have been conducted based on fusion surgery to benefit from these advantages more efficiently and avoid the disadvantages [11][12][13][14].…”
mentioning
confidence: 99%
“…30,43 Nevertheless, it also entails complications such as PS failure and rod breakage. 4446 In this study, it has been shown that the regions of maximum stress concentration for rods and PSs were usually the middle region of the rods and the neck region of the PSs. In the related literature, Guo and Wang 47 demonstrated the same trend for stress concentration regions with rods and PSs.…”
Section: Discussionmentioning
confidence: 67%
“…This technique (and its modifications) was adopted by other authors and has shown encouraging results [4][5][6][7][8][9][10] . Additionally, several studies demonstrated similar biomechanical profiles of transdiscal and classical pedicle screw-based constructs [11][12][13] . In cadaveric biomechanical testing, Minamide et al demonstrated that L5-SLTS pedicle screw-rod system provided a 1.6-1.8 stiffer construct than conventional L5-S1 BPSS.…”
Section: Introductionmentioning
confidence: 88%